2018
DOI: 10.1074/jbc.aw118.003228
|View full text |Cite
|
Sign up to set email alerts
|

Visual cycle proteins: Structure, function, and roles in human retinal disease

Abstract: Here, we seek to summarize the current understanding of the biochemical and molecular events mediated by visual cycle molecules in the eye. The structures and functions of selected visual cycle proteins and their roles in human retinal diseases are also highlighted. Genetic mutations and malfunctions of these proteins provide etiological evidence that many ocular diseases arise from anomalies of retinoid (vitamin A) metabolism and related visual processes. Genetic retinal disorders such as retinitis pigmentosa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 53 publications
(35 reference statements)
0
27
0
Order By: Relevance
“… 43 45 RP is the most common genetically inherited ocular disease and is associated with over 50 different genes. 46 We have identified three genes common to RP and vitamin A. RDH5 and RGR are associated with RP, retinoic acid metabolism, and myopia. RPE65 is common to RP and vitamin A deficiency.…”
Section: Discussionmentioning
confidence: 99%
“… 43 45 RP is the most common genetically inherited ocular disease and is associated with over 50 different genes. 46 We have identified three genes common to RP and vitamin A. RDH5 and RGR are associated with RP, retinoic acid metabolism, and myopia. RPE65 is common to RP and vitamin A deficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Some steps of the visual cycle occur in PR OS but the key step of isomerizing the bond at the 11th carbon of retinal from the trans to cis confirmation is carried out by an isomerase found in the adjacent RPE cells. Interestingly, there is a secondary visual cycle thought to primarily serve cones where the key isomerase is found in the other major support cell for PR, the Muller Glia (Tsin et al, 2018).…”
Section: Gpcr Signaling In Photoreceptorsmentioning
confidence: 99%
“…Functional insights often lag significantly behind initial retinal disease genetic findings because of the complexity of protein activities and the rarity of animal models that fully recapitulate human conditions. Many genes contributing to the visual cycle are associated with inherited retinal diseases such as LCA, rod-cone dystrophy, and a juvenile form of macular degeneration called Stargardt disease (Figure 3) (Hussain et al, 2018;Kiser and Palczewski, 2016;Travis et al, 2007;Tsin et al, 2018). In the simplest case the mutation of a gene can lead to a loss of function (LoF); for example, an inactivating mutation in RDH5 abrogates RDH activity and leads to the disease known as Fundus albipunctatus, characterized by delayed dark adaptation and the appearance of white flecks in the retina (Dryja, 2000;Yamamoto et al, 1999) (Figures 3A and 3B).…”
Section: Genetic Disease-causing Changes In the Visual Cyclementioning
confidence: 99%
“…However, clinical trials on RPE65 gene augmentation therapy showed a significant but modest improvement in retinal function (Bainbridge et al, 2008;Maguire et al, 2008) and fading effects in patients (Maguire et al, 2009). Mutations in the gene encoding the ATP-binding cassette subfamily A member 4 (ABCA4) transporter are the most frequent mutations associated with Stargardt disease and also can cause some forms of autosomal recessive cone-rod dystrophy (not shown in Figure 3) (Paloma et al, 2001;Rozet et al, 1998) and arRP (Allikmets et al, 1997) (reviewed in (Hussain et al, 2018;Kiser and Palczewski, 2016;Molday, 2015;Travis et al, 2007;Tsin et al, 2018;Tsybovsky et al, 2010)). These examples point to the simple fact that mutations in many genes can result in clinically similar disease phenotypes, and that mutations in one gene can manifest in different forms of retinal disease.…”
Section: Genetic Disease-causing Changes In the Visual Cyclementioning
confidence: 99%